Non-collision trajectories of service industrial robots. (October 2018) - Daneshjo, Naqib; Králik, Marián; Majerník, Milan; Pajerská, Erika Dudáš; Naščáková, Jana
Abstract: The innovative algorithm for robot collision testing was developed and debugged for programming industrial robots handling production and peripheral devices in a flexible manufacturing system. Due to this it allows the analysis of the robot effector and robot transition paths with the possibility of optimizing them in relation to the economy of the handling cycle, runway length, safety and operator time and overall handling performance. The key part of our proposal is to analyze the 3D model and its interpretation in a relevant form to enable data processing with modern computer graphics techniques with hardware support of calculations and work at the level of individual objects and polygons. Formalization of the robot's direct and inverse kinematic structure allows control of its interaction during servicing movements with other robot devices and peripherals. This ensures the optimal and unobtrusive trajectory of each mechanical element of the industrial robot serving the production and peripheral devices in the intelligent system.